2015
DOI: 10.1002/rcm.7164
|View full text |Cite
|
Sign up to set email alerts
|

Application of chemometrics to resolve overlapping mass spectral peak clusters between trichloroethylene and its deuterated internal standard

Abstract: This paper describes the first application of CLS to deconvolute overlapping peaks between an analyte and its corresponding isotopic internal standard for quantification. The proposed method enables simple isotopic analogs of analytes (one H or C atom is isotopically labeled) to be used as internal standards for analytes with isotopic distributions. It has wide application because of the environmental impact and prevalence of halogenated VOCs, especially when analytes have isotopic distributions that overlap w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Two regression methods were used for curve fitting in FlavonQ: unweighted and weighted least-squares linear regression. Weighted least-squares linear regression is generally recommended to improve the accuracy of calibration curves at the lower end when the concentration range of calibration is large. , …”
Section: Resultsmentioning
confidence: 99%
“…Two regression methods were used for curve fitting in FlavonQ: unweighted and weighted least-squares linear regression. Weighted least-squares linear regression is generally recommended to improve the accuracy of calibration curves at the lower end when the concentration range of calibration is large. , …”
Section: Resultsmentioning
confidence: 99%
“…In our study, the PA peaks are identified using a UV similarity analysis, where the full UV-vis spectrum (190–600 nm) of each chromatographic peak is compared with that of a reference PA peak or a known PA peak, either endogenous, spiked, or external. Each UV-vis spectrum was normalized to unit vector length before the comparison (Zhang and Harrington, 2013, 2015). The comparison is expressed by the Pearson product-moment correlation coefficient (Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…An external standard calibration curve of catechin was constructed in this study using weighted least squares linear regression with a weighting factor of 1/ x 2 ( x represents concentration) (Zhang and Harrington, 2014; Zhang and Harrington, 2015). It was found that the UV absorbance response of the monomers in molar units was additive for PAs and was not affected by the types of linkages between the flavan-3-ol units (A- or B- type).…”
Section: Resultsmentioning
confidence: 99%
“…However, the application of classical least-squares (CLS) can effectively model the overlapping peaks between an analyte and its corresponding isotopic IS. The details of using TCE-d as an IS for the quantitation of TCE were reported earlier [22]. The calibration was constructed using samples prepared with the same extraction method discussed above with a linear dynamic range of 10-1000 ng mL −1 of TCE in water.…”
Section: Application Of Extraction Methods Using Portable Gc/ms Instrumentioning
confidence: 99%